A case of dissection in an ACUSEAL-modified HeRO graft. Issue 6 (November 2020) - Bradley, N A; Guthrie, G; Suttie, S
Background: The use of the HeRO system with the early-access ACUSEAL graft avoids the need for a tunnelled dialysis catheter as a bridge for vascular access. Established complications of this system include thrombosis, graft infection, haematoma, and pseudoaneurysm formation. Case Description: A 72-year-old patient found to have a dissection flap at the venous cannulation point (ACUSEAL component) of a right arm HeRO graft. The ACUSEAL was replaced in theatre and subsequent duplex imaging confirmed satisfactory graft function. Conclusion: This case demonstrates a serious yet previously undescribed complication of cannulation of an ACUSEAL graft. The trilaminar construction of the graft may increase the likelihood of disruption of the luminal layer during repeated needling and predispose it to dissection. Given the consequences of graft failure in such patients, urgent intervention is warranted when graft dissection is suspected.